Critique of intelligent design : materialism versus creationism from antiquity to the present - Foster, John Bellamy; Clark, Brett; York, Richard, 1971- (New York : Monthly Review Press, 2008)
Critique of Intelligent Design is a compelling account of the debate between materialism and religion as well as an overview of the contemporary fight concerning nature, science, history, morality, and knowledge. The authors demonstrate how historical materialism is a crucial social foundation from which to confront intelligent design. They provide a fascinating account of the development of science in opposition to the proponents of'received wisdom.' --from publisher description
Includes bibliographical references (p. [203]-232) and index.
Keywords: Intelligent design (Teleology); Creationism; Materialism